ANALYSIS OF LEARNING DIFFICULTIES OF ALGEBRAIC CALCULATION OPERATIONS BASED ON NEWMAN'S ERROR TYPE IN BEKASI CITY - Soma Wijaya Rawi; Ishaq Nuriadin (FKIP Universitas Muhammadiyah Tangerang, 2023)
The purpose of this study is to analyze the difficulty of learning algebraic calculation operations based on newman's error type in Bekasi City. This research is a qualitative research involving grade VIII students of Bekasi City. Researchers tried to collect information to analyze the difficulty of learning mathematics on the material of algebraic form calculation operations using the concept of Newman theory. Researchers only took 3 subjects to be the subject of research. At this stage, researchers use research instruments in the form of written tests that contain description questions and algebraic form calculation operations. Data collection by researchers using tests and interviews. The use of qualitative method techniques in analyzing research data shows that there are several factors based on the type of newman error so that they make mistakes doing questions such as, 1) students' answers are considered less thorough, 2) students find it difficult to understand the subject matter of the questions so that students cannot get important information from the questions, 3) students' inability to change story problems into mathematical forms also causes a Students make mistakes in answering questions, 4) students lack understanding of the concept of algebraic material. There are 3 types of difficulties experienced by these students, namely Difficulty in understanding concepts, Difficulty in Solving Verbal Problems, and Difficulty in understanding principles. While there are 5 types of newman type errors, namely, Reading Errors, Wrong Comprehension, Wrong Transformations, Wrong Skill Processes, Drawing Wrong Conclusions.